Efficient alkane oxidation under combustion engine and atmospheric conditions - Zhandong Wang (Nature Portfolio, 2021)
Efficient autoxidation of organic compounds typically requires that they possess double bonds or oxygen-containing moieties, which is why alkanes were thought to contribute little to atmospheric organic aerosol formation. Here, mass spectrometry shows significant autoxidation of alkanes under both atmospheric and combustion conditions.